Perilaku Physical Distancing Mahasiswa UIN Syarif Hidayatullah Jakarta pada Masa Pandemi COVID-19 - Syadidurrahmah, Fidah; Muntahaya, Fika; Islamiyah, Siti Zakiyatul; Fitriani, Tri Aulia; Nisa, Hoirun (UI Scholars Hub, 2020)
Background. The spread of the COVID-19 virus has resulted in unprecedented measures such as restricting travel and social activity in many countries. Physical distancing is critical to fighting COVID-19 and is expected to continue for some time. Objective.The aim of the study was to assess the determinants of physical distancing behavior of university students of UIN Syarif Hidayatullah Jakarta at the beginning of the COVID-19 pandemic. Method. This study used an observational analytic method with cross-sectional study design. A total of 417 respondents was selected by using voluntary sampling method. Information was collected online using google form in April 2020. Data were analysed using a multiple logistic regression test. Results. Good physical distancing behavior carried out by 55.9% of students. The results of multivariate analysis showed that factors associated with physical distancing behavior were female gender (OR=3.438, 95% CI: 2.037-5.804), good knowledge of physical distancing (OR=1.757, 95% CI: 1.057-2.919), and family support (OR=1.854, 95% CI: 1.219-2.819). Meanwhile, support from community leaders was not significantly related to physical distancing behavior (OR=1.469, 95% CI: 0.961-2.246). Conclusion. Uptake of physical distancing behavior needs to increase. Female university students were better at uptaking physical distancing behavior. Family support and knowledge about physical distancing effect the uptake of physical distancing behavior.